Invasive Carcinoma of Breast in a Patient with Neurofibromatosis Type 1: An unusual association – A case report - Bhavya P Mohan; Lailaraji Navamoni; Sankar Sundaram (Tropical Journal of Pathology and Microbiology, 2022)
Neurofibromatosis Type 1 is one of the most common genetic diseases in humans, presenting withmultiple neurofibromas and an increased risk of developing benign and malignant nerve sheathtumors and central nervous system tumors. However, an association between NeurofibromatosisType 1 and breast cancer is unknown. We hereby report a case of invasive breast carcinoma of nospecial type arising in a patient with Neurofibromatosis Type 1.